2002
DOI: 10.17221/4372-pse
|View full text |Cite
|
Sign up to set email alerts
|

Induction of resistance to root rot disease of wheat grown under field condition

Abstract: Four compounds namely Fenor (F-760), Strom, salicylic acid (SA) and thiamin (B 1 ) were tested against root rot disease of wheat under field condition. Wheat grains were soaked in these compounds for 6 h before sowing. Mean disease rating, disease appearance, and distribution of disease were estimated as parameters of disease severity. All tested compounds significantly reduced the root rot of wheat severity during seedling, flowering and ripening stages. Fresh and dry weights were also affected by application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…Application of thiamine hydrochloride (TH) at 1mM in the current study on onion resulted in significant reduction in the bacterial rot diseases throughout storage, the matter which can be explained by the significant increase in the total phenols content and the decrease in the lipid peroxidation and electrolyte leakage in the TH-treated plants comparing with the untreated control plants. These results confirm the successful role of TH in inducing the natural resistance of plant against diseases and agreed with Hashem and Hamada (2002) who used TH for controlling root rot disease of wheat under field condition and found that thiamin significantly reduced the disease severity during seedling, flowering and ripening stage. Also Alhakimi and Alghalibi (2007) used thiamin for controlling broad bean rot disease caused by Fusarium solani and Rhizoctonia solani.…”
Section: Discussionsupporting
confidence: 88%
“…Application of thiamine hydrochloride (TH) at 1mM in the current study on onion resulted in significant reduction in the bacterial rot diseases throughout storage, the matter which can be explained by the significant increase in the total phenols content and the decrease in the lipid peroxidation and electrolyte leakage in the TH-treated plants comparing with the untreated control plants. These results confirm the successful role of TH in inducing the natural resistance of plant against diseases and agreed with Hashem and Hamada (2002) who used TH for controlling root rot disease of wheat under field condition and found that thiamin significantly reduced the disease severity during seedling, flowering and ripening stage. Also Alhakimi and Alghalibi (2007) used thiamin for controlling broad bean rot disease caused by Fusarium solani and Rhizoctonia solani.…”
Section: Discussionsupporting
confidence: 88%